Ergosterol isolated from cloud ear mushroom (Auricularia polytricha) attenuates bisphenol A-induced BV2 microglial cell inflammation. (July 2022) - Sillapachaiyaporn, Chanin; Chuchawankul, Siriporn; Nilkhet, Sunita; Moungkote, Nuntanat; Sarachana, Tewarit; Ung, Alison T.; Baek, Seung Joon; Tencomnao, Tewin
Graphical abstract: Highlights: Mushroom extract and its bioactive component ergosterol attenuated BPA-induced neuroinflammation in BV2 microglial cells. Extracts and ergosterol from Auricularia polytricha demonstrated anti-neuroinflammatory activities by suppressing the NF-kB activity and increasing SOD expression. Extracts from Auricularia polytricha treated on BPA-induced BV2 cells attenuated HT-22 hippocampal cell damage. Abstract: Bisphenol A (BPA) has been reported to have neurotoxic properties that may increase the risk of neurodegenerative diseases by inducing neuroinflammation. Auricularia polytricha (AP) is an edible mushroom with several medicinal properties. Herein, the anti-neuroinflammatory effects of AP extracts against BPA-induced inflammation of BV2 microglial cells were investigated. Hexane (APH) and ethanol (APE) extracts of AP inhibited BPA-induced neuroinflammation in BV2 microglia by reducing microglial activation and the expression of pro-inflammatory cytokines. These anti-inflammatory effects were regulated by the NF-κB signaling pathway. In addition, APH and APE exhibited antioxidative effects by increasing the activity of the SOD-1 enzyme and restoring the accumulation of reactive oxygen species (ROS) in BPA-induced BV2 cells. Moreover, the conditioned medium prepared using BPA-induced BV2 cells demonstrated that the presence of APH or APE could attenuate ROS production in HT-22 cells. Further, ergosterol was isolated from APE and also showed anti-inflammatory and antioxidative activities. In conclusion, AP extracts and ergosterol attenuated neuroinflammation against BPA induction in BV2 microglial cells through the NF-κB signaling pathway.